Finite element analysis of corroded RC beams - Sompura, Meet (My University, 2019)
Reinforcement corrosion has been remained one of the primary environmental factors responsible for RC structure degradation. Rebar corrosion significantly affect the service life of an RC structure. The maintenance and repair work policy should be proactive to restrict corrosion induced damage at optimum cost. Hence it becomes very important to understand the effect of corrosion in an RC beam. A paramount importance has been given to damage assessment of a corroded RC beam. Various experimental investigation has carried out to study the performance of an RC beam due to rebar corrosion. However, the limitations involved with experimental investigations restrict us from having the complete picture of corrosion studies. A 3D nonlinear finite element analysis is an effective tool to simulate the effect of rebar corrosion in an RC beam. A finite element model allows to incorporate various boundary conditions and loading conditions for the corroded RC beam. A comprehensive 3D nonlinear finite element model has proposed for the corroded RC beams. It includes all the primary effects due to rebar corrosion 1) Bond strength degradation, 2) spalling stresses on concrete and 3) Area reduction of the rebar. Finite element model is validated with experimental results. Multiple finite element analysis has performed to find out the effect of rebar corrosion at a constant sustainable load on the RC beam. An optimum maintenance point has proposed to obtain the optimum maintenance and repair work cost for the corroded RC beam. Spalling stress variations has observed with increase of bending stress in a corroded RC beam. An effort has been made to relate the spalling stress variation with global behaviour of the corroded RC beam.
Keywords: finite element analysis; corroded RC beams; sustained loading; spalling stress